2015
DOI: 10.1111/jmp.12178
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protective immune response elicited by a trimeric envelope protein from an Indian clade C HIV‐1 isolate in rhesus macaques

Abstract: Env proteins from a clade C Indian isolate can elicit protective immune response and therefore may be a candidate for inclusion in a multiclade-based HIV-1 vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…There is high level of interest in developing adjuvants that can stimulate potent CD8 and CD4 T cell responses to subunit antigens. Carbomer (acrylic acid polymers)-based adjuvants (CBA) are components of several veterinary vaccines, and known to safely elicit potent neutralizing antibodies to malarial and HIV envelope glycoproteins in mice and nonhuman primates (Menon et al, 2015, Gupta et al, 2014, Anlar et al, 1993. We have also reported that the carbomer-based nano-emulsion adjuvant, Adjuplex (ADJ; Advanced Bioadjuvants), elicits tissue-resident memory CD8 T cells in the lungs, and protects against influenza A virus in mice (Gasper et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is high level of interest in developing adjuvants that can stimulate potent CD8 and CD4 T cell responses to subunit antigens. Carbomer (acrylic acid polymers)-based adjuvants (CBA) are components of several veterinary vaccines, and known to safely elicit potent neutralizing antibodies to malarial and HIV envelope glycoproteins in mice and nonhuman primates (Menon et al, 2015, Gupta et al, 2014, Anlar et al, 1993. We have also reported that the carbomer-based nano-emulsion adjuvant, Adjuplex (ADJ; Advanced Bioadjuvants), elicits tissue-resident memory CD8 T cells in the lungs, and protects against influenza A virus in mice (Gasper et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Insights from such studies might aid in the rational development of adjuvants that can drive potent vaccine-induced T cell responses by engaging monocytes in the lungs. Adjuplex (ADJ) is a carbomer-based nano-emulsion adjuvant that is known to elicit robust neutralizing antibodies to malarial and HIV envelope glycoproteins in mice and nonhuman primates (36,37). We have previously reported that subunit protein formulated in ADJ protects against vaccinia virus and IAV in mice by enhancing DC cross-presentation (38,39).…”
Section: Introductionmentioning
confidence: 99%